Green synthesis of new chiral 1-(arylamino)imidazo[2,1-a]isoindole-2,5-diones from the corresponding α-amino acid arylhydrazides in aqueous medium - Bouzayani, Nadia; Kraїem, Jamil; Marque, Sylvain; Kacem, Yakdhane; Carlin-Sinclair, Abel; Marrot, Jérôme; Hassine, Béchir Ben (Beilstein Journal of Organic Chemistry, 2018)
New chiral 1-(arylamino)imidazo[2,1-a]isoindole-2,5-dione derivatives were obtained in good to excellent yields via the cyclocondensation of 2-formylbenzoic acid and various α-amino acid arylhydrazides using water as the solvent in the presence of sodium dodecyl sulfate as the surfactant and under simple and minimum manipulation, without purification. The reaction is totally diastereoselective and gives access to the nitrogenated tricyclic core with a relative trans stereochemistry.
Keywords: sodium dodecyl sulfate; totally diastereoselective; trans-stereochemistry

Neth. Appl. - Geigy, J. R. (1967)
Chem. Abstr. 1967, 67, 82204q.

Swiss Patent - Graf, W. (1969)
Chem. Abstr. 1970, 72, 100709t.

U.S. Patent - Los, M. (1977)
Chem. Abstr. 1977, 87, 168034j.

U.S. Patent - Ashkar, S. A. (1978)
Chem. Abstr. 1978, 89, 192503y.

U.S. Patent - Ashkar, S. A. (1978)
Chem. Abstr. 1978, 88, 165485s.

U.S. Patent - Ashkar, S. A. (1978)
Chem. Abstr. 1979, 90, 49647p.

(untitled) - Katritzky, A. R.; Mehta, S.; He, H.-Y.; Cui, X. (J. Org. Chem., 2000)

(untitled) - Polniaszek, R. P.; Belmont, S. E. (J. Org. Chem., 1991)

(untitled) - Meyers, A. I.; Seefeld, M. A.; Lefker, B. A.; Blake, J. F.; Williard, P. G. (J. Am. Chem. Soc., 1998)

(untitled) - Burgess, L. E.; Meyers, A. I. (J. Am. Chem. Soc., 1991)

(untitled) - Burgess, L. E.; Meyers, A. I. (J. Org. Chem., 1992)

(untitled) - Katritzky, A. R.; Xu, Y.-J.; He, H.-Y.; Steel, P. J. (J. Chem. Soc., Perkin Trans. 1, 2001)

(untitled) - Katritzky, A. R.; He, H.-Y.; Verma, A. K. (Tetrahedron: Asymmetry, 2002)

(untitled) - Gomes, P.; Araújo, J. M.; Rodrigues, M.; Vale, N.; Azevedo, Z.; Iley, J.; Chambel, P.; Morais, J.; Moreira, R. (Tetrahedron, 2004)

(untitled) - Hosseini-Zare, M. S.; Mahdavi, M.; Saeedi, M.; Asadi, M.; Javanshir, S.; Shafiee, A.; Foroumadi, A. (Tetrahedron Lett., 2012)

(untitled) - Katritzky, A. R.; He, H.-Y.; Jiang, R. (Tetrahedron Lett., 2002)

(untitled) - Kacem, Y.; Kraiem, J.; Kerkeni, E.; Bouraoui, A.; Ben Hassine, B. (Eur. J. Pharm. Sci., 2002)

(untitled) - Aliyenne, A. O.; Khiari, J. E.; Kraïem, J.; Kacem, Y.; Ben Hassine, B. (Tetrahedron Lett., 2006)

(untitled) - Aliyenne, A. O.; Kraïem, J.; Kacem, Y.; Ben Hassine, B. (Tetrahedron Lett., 2008)

(untitled) - Tka, N.; Kraïem, J.; Kacem, Y.; Hajri, A.; Ben Hassine, B. (C. R. Chim., 2009)

(untitled) - Kacem, Y.; Ben Hassine, B. (Tetrahedron Lett., 2012)

(untitled) - Kacem, Y.; Ben Hassine, B. (Tetrahedron: Asymmetry, 2014)

(untitled) - Kacem, Y.; Ben Hassine, B. (Heterocycles, 2014)

(untitled) - Milne, H. B.; Most, C. F. (J. Org. Chem., 1968)

(untitled) - Verardo, G.; Toniutti, N.; Gorassini, A.; Giumanini, A. G. (Eur. J. Org. Chem., 1999)

(untitled) - Verardo, G.; Geatti, P.; Martinuzzi, P.; Merli, M.; Toniutti, N. (Eur. J. Org. Chem., 2003)

(untitled) - Verardo, G.; Toniutti, N.; Giumanini, A. G. (Can. J. Chem., 1998)

(untitled) - Verardo, G.; Geatti, P.; Merli, M.; Castellarin, E. E. (Eur. J. Org. Chem., 2004)

(untitled) - Hoshino, Y.; Oyaizu, M.; Koyanagi, Y.; Honda, K. (Synth. Commun., 2013)

(untitled) - Tundo, P.; Selva, M. (Acc. Chem. Res., 2002)

(untitled) - Rosamilia, A. E.; Aricò, F.; Tundo, P. (J. Org. Chem., 2008)

(untitled) - Kraïem, J.; Ghedira, D.; Ollevier, T. (Green Chem., 2016)

(untitled) - Kraïem, J.; Ollevier, T. (Green Chem., 2017)

(untitled) - Kobayashi, S.; Wakabayashi, T.; Nagayama, S.; Oyamada, H. (Tetrahedron Lett., 1997)

(untitled) - Kobayashi, S.; Wakabayashi, T. (Tetrahedron Lett., 1998)

(untitled) - Manabe, K.; Kobayashi, S. (Synlett, 1999)

(untitled) - Manabe, K.; Mori, Y.; Kobayashi, S. (Tetrahedron, 1999)

(untitled) - Kobayashi, S.; Mori, Y.; Nagayama, S.; Manabe, K. (Green Chem., 1999)

(untitled) - Kobayashi, S.; Manabe, K. (Acc. Chem. Res., 2002)

(untitled) - Landelle, H.; Laduree, D.; Cugnon de Servicourt, M.; Robba, M. (Chem. Pharm. Bull., 1989)

(untitled) - Suzuki, T.; Kubomura, K.; Takayama, H. (J. Chem. Soc., Perkin Trans. 1, 1997)

(untitled) - Bhakuni, B. S.; Yadav, A.; Kumar, S.; Kumar, S. (New J. Chem., 2014)

SADABS, program for scaling and correction of area detector data (Sheldrick, G. M., 1997)

(untitled) - Blessing, R. H. (Acta Crystallogr., Sect. A: Found. Crystallogr., 1995)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Crystallogr., 1990)

SHELX-TL Software Package for the Crystal Structure Determination, 5.03 (Sheldrick, G. M., 1994)

(untitled) - Macrae, C. F.; Bruno, I. J.; Chisholm, J. A.; Edgington, P. R.; McCabe, P.; Pidcock, E.; Rodriguez-Monge, L.; Taylor, R.; van de Streek, J.; Wood, P. A. (J. Appl. Crystallogr., 2008)

(untitled) - Bouzayani, N.; Marque, S.; Djelassi, B.; Kacem, Y.; Marrot, J.; Ben Hassine, B. (New J. Chem., 2018)

(untitled) - Bouzayani, N.; Talbi, W.; Marque, S.; Kacem, Y.; Ben Hassine, B. (ARKIVOC, 2018)